Associations of PM2.5 with Chronic Obstructive Pulmonary Disease in Shipyard Workers: A Cohort Study - Nguyen Thanh Tung; Ching-Huang Lai; Chih-Hong Pan; Wei-Liang Chen; Chung-Ching Wang; Che-Wei Liang; Chi-Yu Chien; Kai-Jen Chuang; Huynh Nguyen Xuan Thao; Hoang Ba Dung; Tran Phan Chung Thuy; Hsiao-Chi Chuang (Aerosol and Air Quality Research)
Abstract The association between lung deposition of particulate matter with an aerodynamic diameter less than 2.5 µm (PM2.5) from welding fumes and lung function is unclear. We conducted a cohort study with a follow-up of 4 years in 115 shipyard workers to investigate the incidence rate of chronic obstructive pulmonary disease (COPD), and to evaluate the effects of welding fume PM2.5 deposition on fractional exhaled nitric oxide (FeNO), lung function, and blood pressure using generalized estimating equation models. Personal exposure to welding fumes was measured, and deposition fractions of inhaled welding fume PM2.5 in lung regions were estimated using multiple-path particle dosimetry. We observed the overall incidence rate of COPD to be 2.51 cases per 100 person-years. The incidence rate was higher in welding workers than in office workers and higher in non-smokers compared to smokers. In the overall cohort subjects, we observed that an increase in the interquartile range of PM2.5 was associated with a 1.618-ppb decrease in FeNO, a 0.115-L decrease in FVC, a 0.091-L decrease in FEV1, a 0.520% increase in the FEV1/FVC ratio, a 0.259-L s−1 decrease in PEF, a 0.096-L s−1 decrease in FEF25%–75%, a 0.215-L s−1 decrease in FEF25%, and a 0.114-L s−1 decrease in FEF50% (all p < 0.05). We observed that a 1-µg m−3 increase in PM2.5 deposition in lung regions (total lung, and head and nasal, tracheobronchial, and alveolar regions) was associated with decreases (β coefficients) in FeNO, FVC, FEV1, PEF, FEF25%–75%, FEF25%, and FEF50% (all p < 0.05). We observed that the absolute values of β coefficients decreased as follows: alveolar > head and nasal > tracheobronchial > total lung regions. Higher incidence rates of COPD were observed in non-smokers and welders, which associated with lung function declines due to PM2.5 exposure. Pulmonary effects by welding fume PM2.5 in occupational settings is an urgent occupational issue for worker health protection.